A Historical Review and Recent Updates on Ichthyofaunal Diversity of Ahilyanagar District, Maharashtra - Ghatge, Swapnil Shivajirao; Balaji Kharatmol; Krishna Patil; Shrikant Jadhav; Mahesh Shetkar; Rohit Hajare (Journal of Indian Fisheries Association, 2024)
A comprehensive and updated inventory of fish species in Ahilyanagar District is crucial for sustainable fisheries, aquaculture, and conservation efforts. This study systematically reviews existing literature, author-collected specimens, and records from the Zoological Survey of India, Pune, documenting 81 fish species across 12 orders and 26 families. Cypriniformes is the dominant order, comprising 43 species (53%). As per the IUCN Red List of Threatened Species, 57 species are assessed as Least Concern, while 2 as Data Deficient, 3 Near Threatened, 3 Vulnerable, and 3 Endangered. Additionally, the inventory identifies 3 transplanted and 10 exotic species. The inventory also updates previous records by eliminating 25 sp. due to taxonomic issues and/or distribution mismatch. This updated dataset serves as a vital reference for researchers, policymakers, and conservationists. aiding in the sustainable management of ichthyofaunal resources and supporting future biodiversity conservation initiatives in the district.